Lexical Valuation Patterns in English and Russian Cultural Contexts: Pola Penilaian Leksikal dalam Konteks Budaya Inggris dan Rusia - Qizi, Pardaeva Farangiza Husniddin (Indonesian Journal of Innovation Studies, 2025)
General Background: Lexical valuation is a key component in understanding language’s affective and cognitive impact across different contexts. Specific Background: Despite extensive research in semantic processing and sentiment analysis, there is limited integration of nuanced lexical perception with value-based interpretation models. Knowledge Gap: Most existing approaches overlook the dynamic interplay between lexical items and their perceived social, cultural, and emotional values. Aims: This study aims to develop a framework for lexical valuation that captures subjective, contextualized interpretations of words beyond traditional sentiment scales. Results: Findings indicate that lexical items carry varying degrees of perceived utility, prestige, and emotional resonance, which are not always aligned with their semantic neutrality or frequency of use. Novelty: The proposed valuation model introduces multi-dimensional scoring that incorporates social, psychological, and functional parameters into lexical assessment. Implications: The framework contributes to linguistics, psycholinguistics, and computational language studies by offering a refined method for modeling word perception, with applications in AI-driven language tools, educational content design, and sociolinguistic analysis.Highlight : Proposes a novel lexical valuation approach combining distributional and curated semantic resources. Emphasizes accurate assessment of word similarity using hybrid models. Benchmarks performance using standardized datasets and evaluation metrics. Keywords : Lexical Valuation, Semantic Resources, Language Modeling, Word Similarity, Evaluation Metrics